RELEVANSI KOLEKSI PERPUS TAKAAN DENGAN KEBUTUHAN INFORMASI PENGGUNA DI PEPRPUSTAKAAN FAKULTAS KEHUTANAN UNIVERSITAS LANCANG KUNING PEKANBARU - Eko Saputra Utama; Nining Sudiar; Vita Amelia (Perpustakaan Nasional RI, 2021)
The purpose of this study is to determine the relevance of library collections to users’ information needs at Forestry Faculty Library, Lancang Kuning University, Pekanbaru. This research uses quantitative approach with descriptive method. The results show that: (1) Current information need approach: 57 respondents searched for collection from scientific aspect, meanwhile in terms of collection availability of Unilak Fahutan Library on current information need, it is found that the most widely provided collection based on cover collection was 454 titles. (2) Everyday information need approach: 50 respondents needed results of researches by lecturers (journals) and by students (theses), meanwhile in terms of collection availability of Unilak Fahutan Library on everyday information need, it is found that the most widely provided collections were books, reports, modules, theses, and journals often used in completing lecture assignments with the total of 1,216 titles. (3) Exhaustive information need approach: 61 respondents needed printed works (books, magazines, reports, etc.), meanwhile the collection availability of Unilak Fahutan Library on exhaustive information need, 886 titles of theses, book journals, proceedings, books, and magazines were available. (4) The need of information at a glance: 64 respondents needed a list of new collection titles to find information, meanwhile in terms of collection availability of Unilak Fahutan Library on the need of information at a glance, it is found that there were 761 titles of brief and clear information such as magazines, bulletin, reports and books.